Mistilinguismo italiano-tedesco in Alto Adige: il caso delle domande coda (Atti del Sodalizio Glottologico Milanese, 2018)
This paper explores research paths in the domain of corpus-based contact linguistics in order to detect regular patterns in the use of languages within bilingual communities, such as the one investigated here (South Tyrol). In particular, a first analysis of tag questions in a bilingual (Italian-German) corpus is presented. The data confirm that a subset of markers, common to both languages, has developed, witnessing the existence of a symmetrical context of languages in contact. KEYWORDS: contact linguistics, bilingualism, Italian, German, tag questions